Differential internalization of amphotericin B - Conjugated nanoparticles in human cells and the expression of heat shock protein 70 - Paulo, Cristiana S. O. (2018)
Although a variety of nanoparticles (NPs) functionalized with amphotericin B, an antifungal agent widely used in the clinic, have been studied in the last years their cytotoxicity profile remains elusive. Here we show that human endothelial cells take up high amounts of silica nanoparticles (SNPs) conjugated with amphotericin B (AmB) (SNP-AmB) (65.4±12.4pg of Si per cell) through macropinocytosis while human fibroblasts internalize relatively low amounts (2.3±0.4pg of Si per cell) because of their low capacity for macropinocytosis. We further show that concentrations of SNP-AmB and SNP up to 400μg/mL do not substantially affect fibroblasts. In contrast, endothelial cells are sensitive to low concentrations of NPs (above 10μg/mL), in particular to SNP-AmB. This is because of their capacity to internalize high concentration of NPs and high sensitivity of their membrane to the effects of AmB. Low-moderate concentrations of SNP-AmB (up to 100μg/mL) induce the production of reactive oxygen species (ROS), LDH release, high expression of pro-inflammatory cytokines and chemokines (IL-8, IL-6, G-CSF, CCL4, IL-1β and CSF2) and high expression of heat shock proteins (HSPs) at gene and protein levels. High concentrations of SNP-AmB (above 100μg/mL) disturb membrane integrity and kill rapidly human cells (60%after 5h). This effect is higher in SNP-AmB than in SNP.